Lin28a expression protects against streptozotocin‐induced β‐cell destruction and prevents diabetes in mice. (18th March 2019) - Sung, Yonghun; Jeong, Jain; Kang, Ri jin; Choi, Minjee; Park, Song; Kwon, Wookbong; Lee, Jinhee; Jang, Soyoung; Park, Si Jun; Kim, Sung‐Hyun; Yi, Junkoo; Choi, Seong‐Kyoon; et al.
Abstract : Lin28, which is highly expressed during embryogenesis, has been shown to play an important role in cell growth and embryonic development. Meanwhile, Lin28 represses let‐7 miRNA biogenesis and block pre‐let‐7 processing in the cytoplasm. The let‐7 family of miRNAs is known to repress oncogenesis and cell cycle progression by targeting oncogenic genes and signalling pathways. Consequently, Lin28 acts as an oncogene by upregulating let‐7 targets through the repression of let‐7 biogenesis. A recent genome‐wide association study (GWAS) showed that many genes related to Type 2 diabetes (T2D) are also oncogenes or cell cycle regulators. The role of Lin28 in mouse growth and glucose metabolism in metabolic‐related tissues has also been studied. In these studies, whole‐body Lin28 overexpression was found to promote glucose utilization and prevent weight gain by inhibiting let‐7 biogenesis. Furthermore, Lin28 has been found to directly stimulate skeletal myogenesis and cell growth. Therefore, we determined whether similar effects mediated by Lin28a, which is essential for cell growth and proliferation, may also apply to pancreatic ß‐cells. We found that overexpression of Lin28a protects pancreatic β‐cells from streptozotocin (STZ)‐induced β‐cell destruction in vitro and in vivo. Furthermore, Lin28a‐overexpressing transgenic (Tg) mice had higher insulin secretion in the presence of glucose than in control mice. Our findings suggest that the Lin28/let‐7 axis is an important regulator of pancreatic β‐cell functions and that precise modulation of this axis may be helpful in treating metabolic diseases such as diabetes. Significance of the study: We demonstrate that Lin28a prevents pancreatic β‐cell death against streptozotocin (STZ)‐induced β‐cell destruction in vitro and in vivo. Furthermore, Lin28a promotes cell survival and proliferation by activating the PI3K‐Akt signalling pathway, which may be dependent on let‐7 regulation. Taken together, our results imply that the Lin28a/let‐7 axis is an important regulator of pancreatic β‐cell functions and that precise modulation of this axis may be helpful in treating metabolic diseases such as diabetes.